Global airline alliances perceived value and quality of life among airline alliances travelers: mediator effects of alliances brand equity and travelers’ experiences / Nor Hisyam Seliman - Seliman, Nor Hisyam (2024)
The travel and tourism sector is recognized globally as key industry contributing to numerous countries' economic growth and well-being in generating revenue. Travel has emerged as a significant Quality-of-Life factor and replaced material objects as a status symbol of wealth and well-being. The airline is one of the important transportations used to fly people from one destination to other destinations to prosper the tourism industry. Nevertheless, one airline cannot transport people to various destinations due to high operational costs; therefore, Global Airline Alliance is formed. Currently, there are three global alliances, namely, the Star Alliance, SkyTeam, and Oneworld. The purpose of these alliances was to create a more consistent, seamless network and revenue sharing. The International Air Transport Association has identified 274 airlines that are currently operating in over 117 countries. Out of 274 airlines, 58 have joined the alliances. This study examined the effect of Global Airline Alliances Perceived Value toward Alliances Brand Equity, Travelers’ Experiences, and Travelers’ Quality of Life using a quantitative approach. The Global airline alliance’s perceived value consists of six dimensions: Perceived Network Extension, Perceived Frequent Flyers Program, Perceived Price Competitiveness, Perceived Psycho-socio, Perceived General Attitude and Perceived Safety and Security. Data was collected at Kuala Lumpur International Airport and via social media using convenience sampling. A total of 262 usable responses representing airline alliance travelers who have travelled for the past 6 months with any global airline alliances were successfully analyzed using PLS-SEM. This study found that airline alliance perceived value positively influenced airline alliance brand equity while travelers’ experiences influence travelers’ quality of life. Additionally, travelers’ experiences were found to mediate global airline alliances' perceived value with travelers’ quality of life. Nevertheless, global airline alliances perceived value and airline alliances' brand equity do not influence travelers’ quality of life. Findings from this study provide valuable insights for airline alliances members to understand travelers’ needs and demands so that they can better strengthen their business strategy, use the unadvertised benefits of the alliance as their marketing promotion, and enhance the travelers’ experiences starting from the purchasing of the ticket until arriving at their final destinations. Theoretically, this study made relevant contributions to the global airline alliances' perceived value, travelers’ quality of life literature, and theories. The limitations of the study have been identified, such as the risk of losing out on big-picture details on the variable used due to the quantitative approach used and focusing only on the six dimensions of global airline alliance perceived value. Future research is encouraged to use the qualitative approaches and tap on other dimensions of global airline alliance perceived value so that a more holistic picture can be obtained to explain the study.